Change in the Category of Land for Agricultural Purposes - Aleksandrovich Mayboroda, Victor (International Journal of Engineering and Technology, 2018)
This article is based on the comparative analysis of civil, land and urban planning legislation. It reveals inconsistency in the regulatory planning of agricultural land use in case of changing its category. As a rule, the subsequent use of agricultural land for different purposes usually leads to fertility loss. This reproduction method has no price and is not expressed in monetary terms. The criteria for determining the value of land used by the Russian legislation are off-market surrogates. In this regard, they are used to transform the value of the land without market turnover into the value of land plots that are characterized by certain market conditions and high demand. Thus, the author of the article suggests supplementing the revealed shortcomings of established regulatory practices with the SEEA accounting system developed by the United Nations Organization to evaluate natural-ecological objects. SEEA (or a similar tool) is used for changing the category of agricultural land as a means of saving land fertility for future generations.Â Â